2021
DOI: 10.3390/ijms22169022
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Pathways and Downstream Effectors of Host Innate Immunity in Plants

Abstract: Phytopathogens, such as biotrophs, hemibiotrophs and necrotrophs, pose serious stress on the development of their host plants, compromising their yields. Plants are in constant interaction with such phytopathogens and hence are vulnerable to their attack. In order to counter these attacks, plants need to develop immunity against them. Consequently, plants have developed strategies of recognizing and countering pathogenesis through pattern-triggered immunity (PTI) and effector-triggered immunity (ETI). Pathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 168 publications
0
16
0
Order By: Relevance
“…Disease assays revealed that loss-of function of ONAC096 in ONAC096-CP and onac096 plants exhibited decreased while overexpression of ONAC096 strengthened resistance to M. oryzae and Xoo (Figures 3, 4 and Supplementary Figure 4). PTI is the first layer of immune response in plants, which can be triggered via activation of PRRs by chitin, flagellin or other elicitor, accompanying a set of signaling cascades including ROS burst and induction of PTI-related defense genes (Wang et al, 2019;Kumar et al, 2021;Yuan et al, 2019b;Yuan X. et al, 2021). Overexpression of ONAC096 triggered while knockout of ONAC096 suppressed chitin-or flg22-induced ROS burst and PTI marker gene expression (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disease assays revealed that loss-of function of ONAC096 in ONAC096-CP and onac096 plants exhibited decreased while overexpression of ONAC096 strengthened resistance to M. oryzae and Xoo (Figures 3, 4 and Supplementary Figure 4). PTI is the first layer of immune response in plants, which can be triggered via activation of PRRs by chitin, flagellin or other elicitor, accompanying a set of signaling cascades including ROS burst and induction of PTI-related defense genes (Wang et al, 2019;Kumar et al, 2021;Yuan et al, 2019b;Yuan X. et al, 2021). Overexpression of ONAC096 triggered while knockout of ONAC096 suppressed chitin-or flg22-induced ROS burst and PTI marker gene expression (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…To defend themselves against potential pathogens, plants have evolved a complicated and fine-tuned innate immune system, which consists of pattern-triggered immunity (PTI) and effectortriggered immunity (ETI) (Jones and Dangl, 2006;Boller and He, 2009;Zhou and Zhang, 2020). PTI is the first layer of immune response that is initiated upon perception of conserved PAMP/MAMP/DAMP by cell surfacelocalized pattern recognition receptors (PRRs) (Boller and Felix, 2009;Kumar et al, 2021). ETI is the second layer of immune response that is stimulated upon direct or indirect recognition of pathogen-secreted effectors by intracellular resistance proteins (Jones and Dangl, 2006;Zhou and Zhang, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the ideal banana leaf that is inserted is from the banana plant, which does not bear the fruits. The wounds or the damage on the leaf surface caused by insects or environmental, mechanical damage, such as rain and wind, can be the potential routes of bacteria to enter the leaves in addition to the natural openings [32]. Therefore, selecting the whole, undamaged leaves as filters on the cloth face masks is highly recommended.…”
Section: Bacterial Filtration Efficiency (Bfe) Test On Masks With Lea...mentioning
confidence: 99%
“…Based on the N-terminal structures, NLR proteins can be classified into two categories. TIR-NLR (TNLs) contain the toll/interlcukin-1-reccptor (TIR) region and CC-NLR (CNLs) contain coiled coil (CC) domain [9][10][11][12][13][14][15].…”
Section: Plant Immunity 1pti and Etimentioning
confidence: 99%